Faunal survey, endemism and possible species loss of Scarabaeinae (Coleoptera: Scarabaeidae) in the western slopes of the moist South Western Ghats, South India - Sabu, Thomas K.; Nithya, S.; Vinod, K. V. (Zootaxa, 2011)
Species composition, distribution patterns and endemism are outlined for the dung beetles in the ecoregions of the western slopes of the moist South Western Ghats, South India. Among the 142 dung beetle species known, 35 are endemic to the Western Ghats; 29 are endemic to the moist South Western Ghats; 25 are regionally endemic to the South Western Ghats montane rain forests ecoregion; and one each to the Malabar Coast moist deciduous forest ecoregion and the South Western Ghats moist deciduous forests ecoregion. Five species, including the 3 flightless species, are local endemics to the upper montane tropical montane cloud forests. The montane rain forests ecoregion has the highest number of endemics in the moist south Western Ghats and the moist deciduous forests ecoregion and Malabar Coast moist deciduous forest ecoregion have the lowest levels of endemism. Of the 137 dung beetle species known prior to the deforestation and habitat modification of the region, only 87 have been collected recently.